DIMENSI DAN KOMPOSISI NEMATOSIT PADA KARANG SCLERACTINIA, Acropora florida DAN Acropora divaricata DI PANTAI MOTANDOI SELATAN KABUPATEN BOLAANG MONGONDOW SELATAN - Sanjay Gagu; Suria Darwasito; Billy Th Wagey; Antonius P Rumengan; Ari B Rondonuwu; Carolus P Paruntu (JURNAL PESISIR DAN LAUT TROPIS, 2019)
The purpose of this study was to determine the type, dimensions and composition of nematocytes in Scleractinia, Acropora florida and Acropora divaricata.  This research was conducted in South Motandoi Beach, East Pinolosian District, South Bolaang Mongondow Regency, North Sulawesi for five (5) months; from February to June 2019.  The method of this research was observation using student-t statistical data analysis. Microbasic p-Mastigophore type-II (MpM-II) and Holotricous isorhiza (HI), while A. divaricata only has type-II Microbasic p-Mastigophore (MpM-II) nematocytes.  The nematocytes dimension showed an average capsule length of MpM II in A. florida of was 262.32 µm and A. divaricata was 125.15 µm, mean capsule width of MPM II in A. florida was 67.01 µm and A. divaricata was 31.95 µm, and the average length of mpM II on A. florida was 154.44 µm, and A. divaricata was 70.97 µm.  Nematocytes composition showed that MPM II in A. florida was 95.56% and HI was 4.44%, while the composition of MPM II nematocytes in A. divaricata was 100% and HI was 0%.  Student t-test showed that the ratio of 2 average values of capsule length, capsule width, and MPM II stem length from two populations of A. florida and A. divaricata were not significantly different (P> 0.05).   It can be concluded that both types of A. florida and A. divaricata corals have different types and composition of nematocytes however their size dimensions are not significantly different.  Further studies are important to examine genetic and environmental factors to find out how much the kinship relationship between the two types of those coral.Keywords: Acropora florida, Acropora divaricata, HI, Scleractinia coral, MpM II, nematocytes